Diskurskonstruktionen und Selbst: Eine kognitionslinguistische Perspektive auf Literatur und Realität vom 17. Jahrhundert bis zur Gegenwart - Mucha, Katharina (transcript, 2018)
This study explores the role language plays when it comes to design realities and imaginations - and provides a suggestion for appreciative discourses and creativity.